Awareness and use of online information sources among University of Ibadan students (2017)
The internet has helped in the amassing of a large amount of information for consumption in varied fields of endeavor. This has brought about increasing ease in the search for and use of information in academic, social, political and other spheres of life. However, despite the increasing simplicity in the accessing of information, there are indications that some students do not fully utilize information sources. Thus, this study investigates the awareness and use of online information sources among university of Ibadan undergraduate students. Copies of questionnaires were administered on 300 students on purposive sampling basis. Findings show that 97.9% of the students were generally aware of online information sources but very few of the students were aware of the individual online sources that are made available in the university. In addition, very few of the students were satisfied with the available online information sources. This study suggests that university libraries should effectively create awareness about the various online resources that available for students’ usage. The findings of this study will be useful to academic institutions in the same terrain like the University of Ibadan. Also, librarians and academic scholars will find this study useful in the effective creation of awareness of online information sources among university students.